Study to Assess Knowledge of Mothers Regarding Importance of Play for Children (International Journal of Nursing Education, 2019)
Play is “work” for young children and is understood to build necessary cognitive, physical, social , language and emotional well-being of children. Play also offers an ideal opportunity for mothers to engage fully with their children. This thesis project, explores the subject of play within the early childhood considering both cognitive and social constructivism. The multiple purpose of the project was to gain a more complete understanding of the importance of play in the early childhood , emphasizing on children’s intellectual, physical ,emotional and social growth, pertaining to play and in order to establish guidelines regarding the importance of play, role of mothers in their play & type of play material for children in early childhood.